The rhetorical purposes of declarative and interrogative styles in the fifth poem T (Condemning the world and learning from those who have passed): A critical rhetorical study - Ahmed, Asst. L. Khonche Sabah (Sulaimani Journal for Humanities, 2024)
Poetic discourse is of paramount importance in persuasion, influence, and enjoyment. The significance of this research stems from its aim to study the rhetorical purposes of declarative and interrogative styles in the fifth poem of Sheikh Muhammad al-Nudhi, demonstrating his ability to persuade, influence, and entertain, and highlighting some rhetorical aspects of his poetic style. The researcher employed a descriptive-analytical approach to elucidate the rhetorical purposes of these styles. The researcher developed a plan to achieve the research objectives, comprising an introduction, three sections: the first section addresses the life, poetry, and works of Sheikh Muhammad al-Nudhi; the second section examines the rhetorical purposes of interrogative styles in his fifth poem; and the third section explores the purposes of declarative statements in the fifth poem. The research concludes with a summary of the most important findings and recommendations. Among the key findings is that Sheikh Muhammad al-Nudhi possesses a remarkable ability to employ declarative and interrogative styles in his poetic discourse, effectively achieving the goals of communication and enjoyment. Furthermore, the declarative styles outweigh the interrogative styles in the poem, thus achieving both communication and intentionality within the text. The rhetorical devices in the text are varied despite its brevity, and the purposes of Sheikh Muhammad Al-Nudhi's poetic discourse were intended for very precise goals. The researcher recommends studying Sheikh Muhammad Al-Nudhi's poetic discourse according to modern rhetorical and critical approaches in order to demonstrate the value of his poetic texts and to clarify his expressive tools and methods of argumentation.
Keywords: The Nodehi; informative styles; and construction styles